Evaluation of the Association Between Maternal Periodontal Health and Preeclampsia - Roya Shariatmadar Ahmadi; Arefe Lor; Ferena Sayar; Maryam Kashanian; Samira Hajisadeghi (Islamic Dental Association of Iran, 2018)
Abstract Background and Aim: Preeclampsia is a considerable complication of pregnancy. Chronic inflammations such as periodontitis may lead to a transient low-grade bacteremia in the maternal-fetal circulation, inducing systemic immune responses, placental abnormalities, and other clinical manifestations of preeclampsia. There are inconsistent findings regarding the correlation between periodontitis and preeclampsia. The aim of this study was to compare periodontal parameters in preeclamptic and normotensive pregnant women. Materials and Methods: This case-control study was conducted among pregnant women visiting Akbarabadi Teaching Hospital, Tehran, Iran, for specialized care during 2015-16. From among 260 pregnant women, 100 with gestational hypertension were selected as the case group, and 100 without gestational hypertension were recruited as the control group. The examined periodontal parameters included Probing Depth (PD), Clinical Attachment Loss (CAL), Bleeding on Probing (BOP), and Plaque Control Record (PCR). The participants' demographic data, prenatal history, and family history were collected through interviewing and assessing their medical records. Data were analyzed by Mann-Whitney U test. Results: Although there were significant statistical differences between the groups with regards to the mean ± standard deviation (SD) of PD (P<0.0001), CAL (P<0.0001), PCR (P=0.001), and BOP (P=0.016) indices, yet the differences were clinically smaller than 0.3 mm and could not be measured with a periodontal probe. Also, the percentage of periodontal diseases was 98% in preeclamptic women and 93% in normotensive women (P=0.17). Conclusion: The present study did not support the theory of the relationship between periodontal parameters and preeclampsia.